КОЛОВРАТКИ СЕМЕЙСТВА EUCHLANIDAE EHRENBERG, 1838 ФАУНЫ УЗБЕКИСТАНА - Сапаров, А.Д.; Мирабдуллаев, И.М. (SCIENCE and SOCIETY, 2019)
Four genera and ten species have been recorded in the waterbodies of Uzbekistan: Eudactilota (1 species), Tripleuchlanis (1), Dipleuchlanis (1), Euchlanis (7). They are planktonic and bentho-planktonic freshwater species. Short descriptions and tables for determination of species of the family Euchlanidae of the fauna of Uzbekistan are presented. Genus Eudactilota – toes are longer than the length of the body, members of the leg are well separated, lorica soft. Genera Dipleuchlanis, Euchlanis, Tripleuchlanis – toes shorter than half the length of the body, members of the leg are short, unclearly separated, lorica rigid. Genus Tripleuchlanis – dorsal and ventral plates about of the same length, connected by deep double longitudinal furrows. Genus Dipleuchlanis – dorsal plate shorter then ventral one, furrows always deep. Genus Euchlanis – dorsal plate longer then ventral, furrows sometimes unclearly developed or absent. Posterior margin of dorsal plate of lorica with deep V- or U-shaped notch – Euchlanis oropha (leg toes relatively short, swollen in the middle part), E. incisa (dorsal plate with high longitudinal keel), and E. dilatata (dorsal plate without a keel). Posterior margin of dorsal plate of lorica round, or with small middle notch or extended in sharp angle – E. triquetra (dorsal plate with high longitudinal keel; posterior margin of dorsal plate of lorica extended in sharp angle), E. lyra (lateral longitudinal furrows present), E. deflexa (lateral longitudinal furrows absent, toes of leg thick, sometimes slightly swollen), E. pyriformis (lateral longitudinal furrows absent, toes of leg slim, with almost parallel lateral sides).